On The Derivation Of Swahili 'amba' Relative Clauses: Evidence For Movement - Gould, Isaac; Scott, Tessa (My University, 2019)
This paper brings together two disparate strands of research in the literature on relative clauses (RCs) in Swahili. Our focus is to provide a unified analysis of various data involving a particular kind of head-external RC, namely amba-RCs. Our interest is in whether these RCs involve movement of the head from inside the RC to its external position (i.e. head raising). To investigate this, we look at scope interactions between a quantified RC-head and some other quantifier. We propose a diagnostic test using constraints on long-distance QR (LDQR) from Fox (2000) to provide evidence for the following claims: amba-RCs involve head raising, and amba-RCs are not islands for overt syntactic movement.
Keywords: Swahili relative clauses; long-distance Quantifier Raising; scope economy